Beyond industrial standards: crafting quality bread with heritage wheat in Walloon alternative bread supply chains - Lou Chaussebourg; Florian Baijot; Noémie Maughan; Marjolein Visser; Kevin Maréchal (Frontiers in Sustainable Food Systems, 2025)
Echoing a transformative perspective of agroecological transitions, alternative bread supply chains (ABSCs) experiment with technical and social innovations to overcome the limitations of industrial baking through artisanal knowledge. Yet, ABSCs in Wallonia, Belgium, face specific challenges as the heritage wheat varieties they use, while adapted to local conditions, do not meet industry-defined “baking value” standards and are thus deemed unsuitable for bread-making. This study demonstrates that artisanal bakers can effectively use these flours, challenging traditional notions of flour “quality” in terms of nutrition and flavor versus workability. In this study, nine types of flour were analyzed using measures from industrial standards: protein content, water content, α-amylase activity, and baking strength. These flours were sourced from six heritage wheat varieties, two variety mixes (one field-based, one post-harvest), and one modern variety bred for organic agriculture, all grown on the same field and milled under the same conditions. These varieties are used by farmers in Wallonia ABSCs, showing their relevance to the local conditions. Their poor industrial ratings were then put to the test by three artisanal bakers, who baked and assessed each flour using sensory-based evaluation tables before, during, and after baking. Semi-structured interviews provided insight into bakers’ strategies for handling these flours and went further in the understanding of why artisanal bakers could even prefer allegedly unsuitable flours from heritage varieties than standard flours, easier to bake. Findings reveal that ABSCs bakers employ complex craft techniques, drawing on sensory awareness and intuitive adaptation to address the variability of heritage flours. This artisanal perspective—viewing raw materials as “living matter”—and its set of related skills should thus be promoted in apprenticeship as they are seen essential for a wider agroecological transition of food systems. These practices contributing to processes of scaling deep sustainability initiatives, that aim to reshape values and narratives of the broader system. Such perspectives would indeed contribute to reshaping values and narratives, a dynamic that is crucial to support for amplifying the broader transformative potential of ABSC.